Pharzolution Prototype Design: Problem Solving Applications Using Figma for Pharmaceutical Problems in the Jabodetabek Area - Wildani Zakiyah; Indah Laily Hilmi; Devi Ratnasari (IJISTECH (International Journal of Information System and Technology), 2022)
Today's technology users are very diverse, namely from the younger generation, parents, experts, and ordinary people. Based on the results of the 2019 PISA survey on the world's education system, Indonesia is located in a low position at 74th out of a total of 79 countries. Based on research conducted in Sleman district, public knowledge about self-medication is still at a low level of 52.9%. Finding a job is not an easy thing in Indonesia. Pharzolution is a SaaS-based application to address issues of education, drug use, and information on job vacancies in the pharmaceutical sector. Respondents were made to 15 people consisting of 5 Pharmacy Vocational High School graduates, 5 Pharmacy D3 graduates or S1 Pharmacy graduates, and 5 pharmacists in the Jabodetabek area by applying the design thinking process to find out problems and solve appropriate solutions. Through interviews, the results obtained 6 suggestions that form the main features of the pharzolution application. The process of compiling the user interface display and user experience prototype is carried out through the figma website. The business model design process uses lean canvas which is an adaptation of the business model canvas. Pharzolution has 3 main features, namely pharducation, drug algorithm, and pharjobs